2015
DOI: 10.1109/jsen.2015.2409884
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Synthetic Aperture Radar Imaging of Nonuniformly Rotating Target Based on the Parameters Estimation of Multicomponent Quadratic Frequency-Modulated Signals

Abstract: Inverse synthetic aperture radar (ISAR) is very useful in radar signature applications. In ISAR imaging of nonuniformly rotating target, the radar echo signal in a range cell can be modeled as multicomponent quadratic frequencymodulated (QFM) signals. The high-quality radar images can be obtained by the parameters estimation of QFM signals combined with the range-instantaneous-Doppler technique. In this paper, a novel algorithm for the parameters estimation of QFM signal via the modified cubic phase function (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Then, Radon transform as (10) is applied to detect the line. (10) where, k is the intercept, and θ is the bevel. After Radon transform, the line in v − t domain is projected to be a peak in k − θ domain.…”
Section: Cubic Chirplet Decomposition Based On Radon Transformmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, Radon transform as (10) is applied to detect the line. (10) where, k is the intercept, and θ is the bevel. After Radon transform, the line in v − t domain is projected to be a peak in k − θ domain.…”
Section: Cubic Chirplet Decomposition Based On Radon Transformmentioning
confidence: 99%
“…The ship's 3-D rotations are utilized to obtain the resolutions in the "chirp rate" direction and the "cubic rate" direction. To estimate the "chirp rate" and the "cubic rate", we propose a cubic chirplet decomposition algorithm based on Radon transform, which is proved to have a better precision compared with the existing cubic phase term estimation algorithms, such as Keystone timechirp rate distribution (KTCRD) [9], modified cubic phase function (MCPF) [10], and generalized scaled Fourier transform (GSCFT) [11]. After these parameters are estimated, the "crude" 3-D ISAR image can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of transforming non-uniform rotation into uniform rotation through suitable for imaging of a real target. Wang et al [24,25], Li et al [26], and Liu et al [27] indicated that the non-uniform rotation of the target leads to multiple LFM or PPS components in cross-range signals, and used the slow time resampling approach for rotational nonuniformity compensation. However, the coefficient estimation of the PPS is not very accurate due to noise and mutual interference, which adversely affect the following slow time resampling and final ISAR imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the ability to produce high-resolution microwave imagery for the non-cooperative target nearly regardless of weather condition, the inverse synthetic aperture radar (ISAR) presents a range of applications in the field of national defense surveillance [1,2,3,4]. The range-Doppler (RD) ISAR imaging algorithm [5,6] can be an effective means to obtain radar images, provided that the Doppler frequency shift is constant during the imaging time.…”
Section: Introductionmentioning
confidence: 99%